The importance of learning the history of modern architecture - Meléndez-Rodríguez, Lenin John (2021)
The research work describes the importance of learning about the history of modern architecture, in circumstances that are considered outdated and postmodern architecture is emphasized, its presence and future inheritance are ignored. A quasi-experimental design was applied in which 18 students from the 2018-II History Seminar of the Faculty of Architecture of the National University of the Center of Peru participated as population and sample analysis units. The instrument was the meaningful verification learning questionnaire. The results show the association of the new information with that which the students possessed and started in the subject in the dimensions of declarative and procedural knowledge, internalizing the concepts of the antecedents, development and continuity of modern architecture. Demonstrating the importance of learning modern architecture because it provided new capacities to solve their academic and future project proposals.